Linguopragmatic Neutralization of the Gender Aspect in the Academic Discourse of English-Speaking Countries - Kseniya A. Melnikova (Вестник Северного (Арктического) федерального университета: Серия «Гуманитарные и социальные науки»)
Nowadays, effective communication is one of the primary goals of a modern person. In particular, successful communication is determined by the pragmatics of linguistic means used by communicators. Despite the presence of neutralized vocabulary in all spheres of discourse, the phenomenon of linguopragmatic neutralization is still understudied. The use of neutralized vocabulary in the English-language academic discourse deserves special attention since the exchange of information and dissemination of scientific knowledge are not only major goals of education, but also guarantees of the progressive development of scientific and technological sector. This knowledge exchange is done primarily in English, which is a language of international communication. The author analysed authentic materials from official websites of Western universities containing recommendations on composing and writing texts that can be attributed to the genre of academic discourse (academic essays, graduate qualification papers, etc.). It was found that most educational institutions suggest using so-called inclusive language, based on the principle of political correctness. According to the results, the most effective ways of neutralizing discriminatively marked lexical units in academic discourse are the non-use of gendered pronouns, replacement of gendered pronouns with articles, use of passive instead of active voice constructions, use of plural pronouns to denote one person, use of gender-neutral pronouns, and transformation of gendered address. Thus, neutralization in academic discourse is primarily applied when dealing with gender identity, which may be due to the changes in the socio-cultural life of society and the attitude of society towards the problems of discrimination and social inequality.